Drug-Induced Acute Interstitial Nephritis - Sirisuksakun, Chumphon; Satirapoj, Bancha (Journal of the Nephrology Society of Thailand, 2023)
Acute interstitial nephritis (AIN) is an important cause of acute kidney injury. Antibiotics, proton-pump inhibitors, and non-steroidal anti-inflammatory drugs (NSAIDs) are relatively common causes of drug-induced AIN. The pathogenesis of drug-induced AIN involves an allergic response resulting in drug hypersensitivity. The typical triad of symptoms, i.e., rash, fever, and eosinophilia, is only found in 10% of the patients. AIN develops weeks or months after the initiation of the medications. Therefore, drug-induced AIN should be considered in patients with unexplained acute kidney injury and subsequent tissue diagnosis is required. The principles of treatment include the rapid removal of culprit medications and considering for initiation of immunosuppression to reduce chronic kidney disease progression. To date, the efficacy of corticosteroids for treatment of drug-induced AIN has been evaluated in only observational studies. High-dose corticosteroids should be considered in patients with high-probability of responses including the history of recent uses of the responsible drugs, and mild to moderate interstitial fibrosis from kidney biopsies. Corticosteroids should be discontinued if no meaningful improvement in renal function after 8 weeks because they may potentiate adverse reactions without adding more benefits.